O PAPEL DO COORDENADOR PEDAGÓGICO NA FORMAÇÃO DOS PROFESSORES - Silva, Adalberto (2012)
This dissertation in the field of education, is central is the job of coordinating education at school, work that is being improved to over the past years, given the evolution of education and awareness about the need for continuing education by teachers and management team on behalf of better qualified professional and hence the quality of teaching. As a research problem was posed the question: what is the role of coordinating education in the ongoing training of teachers and that this results in greater social and political commitment to education? Among the hypotheses that guided the study are the following: the role of the coordinator can avarice the construction of a joint work, that aims to promote the autonomy of school staff, enriching the professional practice and providing an experience-sharing exercise, the exercise of dialogue promotes the overcoming of obstacles and partnership between the school coordinator and his team, so that, when shared, problems can be transformed into stimuli to search for new paths, Continuing Education can be a good alternative to the coordinator, in the exercise of its function, prepare school staff, especially teachers, to progressively assume autonomous attitudes in the face of conflict that interfere in the process of teaching and learning. The overall objective of the study was to research the political and social commitment of the educational coordinators Maua town with education. Among the specific objectives the following points: to present a historical approach on the pedagogical coordinator; competence analyze the pedagogical coordinator, to analyze the trajectory of the training coordinator for learning, and discuss the importance of training for the pedagogical coordinator. Besides the theoretical basis in search of the proposed objectives, the study included field survey, qualitative, interviews with pedagogical coordinators and teachers, and the results, in general, will meet the assumptions made, especially for coordinating the work of teaching in constructive dialogue between the team and ways to formation continuing requirement of this extremely essential in education and society.